Differences in loading and morphological structure of the take-off and non-take-off limb in athletics jumping events - Kutác, P.; Uchyti, J. (Journal of Human Kinetics, 2018)
The objective of the study was to assess differences between the take-off and non-take-off limbs of athletes in track-and-field jumping events based on a segmental analysis of body composition as well as kinetic analysis. The research included 19 participants (10 males, 9 females) with an average age of 18.1 ± 2.8 years. We measured body height, body mass, body composition (body fat, fat free mass, bone mineral content and bone density) and segmental distribution of these variables. To assess strength of the lower limbs, we performed reaction force analysis during take-off and run symmetry. The difference in the representation of soft tissues between the take-off and non-take-off limbs was not significant; the differences were 0.06%, 0 kg in body fat and 0.01 kg in fat free mass. The differences in the values of bone matter were significant. The bone mineral content was 0.05 kg higher in the take-off limb (p < 0.001), and bone density was 0.07 g/cm2 higher (p < 0.001); the practical significance of the difference was intermediate (d = 0.5). Kinetic analysis showed that athletes exerted greater force on the pad with the take-off limb than the non-take-off limb when taking off while using arms in the first peak of the vertical force. The difference determined in this type of take-off was statistically significant (p < 0.05); the practical significance of the difference was medium (d = 0.7). The difference in the second peak of the vertical reaction force in the take-off arm was not statistically significant. The differences were reflected in the different bone matter compositions.